An Experimental Investigation into Chosen Parameters of Diesel-Water Emulsion on Combustion Processes - Pradeep Kumar Arokiasamy Remigious; Annamalai Kandasamy; Premkartikkumar Selvi Rajaram (Journal of Chemistry)
The purpose of this research is to investigate the effect of mixing water with diesel to make an emulsified fuel considering the needs for the vehicle performance and its cleanest possible operation. The test fuels chosen for the investigation are termed Emulsion 1 (EM1) and Emulsion 2 (EM2). EM1 is prepared in the ratio of 91/8/1 which represents 91% diesel, 8% water, 0.5% surfactant (Span 20), and 0.5% cosurfactant (Tween 20) with continuous stirring. EM2 has a composition of 94% diesel, 5% water, 0.5% Span 20, and 0.5% Tween 20. The stability of the emulsified fuel is checked for 8 hours. The performance and emission characteristics of EM1 and EM2 are compared with diesel fuel. The emission parameters such as hydrocarbon emission, carbon monoxide (CO) emission, smoke opacity, and oxides of nitrogen (NOx) emission have been measured. To compare the difference in performance characteristics between diesel fuel and emulsified fuel, brake thermal efficiency has been taken into account as a measure. Appreciable reductions of emission parameters have been obtained, and hence the investigation assures that this research could be further extended to biodiesel fuel as it produces more NOx than diesel fuel.